Herpes Zoster in Two Healthy Children - Kokcam, Ibrahim; Dilek, Nursel (Galenos Yayincilik, 2009)
Herpes zoster is an acute dermatomal viral infection caused by the reactivation of varicella zoster virus. The disease is commonly seen among elderly people and immunocompromised individuals, it is also rarely observed in immunocompetent children though. In this report, two herpes zoster cases with trigeminal-involvement in which no factors inducing the reactivation of the virus were detected are presented, as the disease is unusually seen during childhood.
Sa?hkli i?ki çocukta herpes zoster
Keywords: Herpes zoster; Herpes zoster oticus; Herpes zoster ophthalmicus; child; acyclovir